Geological Structure and Evolution of Kefallonia and Ithaki islands - ΛΕΚΚΑΣ, Ε.; ΔΑΝΑΜΟΣ, Γ.; ΜΑΥΡΙΚΑΣ, Γ. (Bulletin of the Geological Society of Greece, 2001)
This paper deals with the geological formations and the fades of the sediments that appear in Kefallonia and Ithaki islands. Kefallonia is built by formations that belong to the units of Paxos and Ionian while Ithaki is mainly dominated by carbonate sediments of Ionian unit. Furthermore, younger formations lay uncomformably upon the previous alpine formations while both in Kefallonia and Ithaki islands a lower marine and an upper continental sequence are observed. The structure of Kefalonia and Ithaki islands is the result of a string of successive tectonic compressional episodes, among which extensional episodes that hosted gravitational movements have taken place. These tectonic compressional episodes are characterised by reverse faults, thrusts and folds while structures due to gravity correspond to faults with normal or oblique-normal offset. Strike slip faults are also present. On both sides of fault surfaces, block movements are responsible for shoreline uplift or submergence, remarkable incision on upthrown blocks, deflection of drainage network, and so on. Each block is particularly described below. Based on the geometric and kinematic data of tectonic discontinuities, the main stages of Kefallonia and Ithaki islands tectonic evolution are presented from the Up.Miocene - L.Pliocene until the Present.